Aspectos fisiológicos e imunológicos de Pythium insidiosum e atividade de antimicrobianos frente a Conidiobolus lamprauges - Tondolo, Juliana Simoni Moraes (2016)
Conidiobolomycosis and pythiosis are important infections that affect animals and humans, which presents difficulties in diagnosis and treatment. The conidiobolomycosis is caused by the fungi Conidiobolus coronatus, C. incongruus and C. lamprauges, affecting sheep, horses, dogs and humans; pythiosis is caused by the oomycete Pythium insidiosum and affects wild and domestic mammals, particularly horses and humans. There is no standard pharmacological approach to the treatment of infections and the surgical rescission is a method often needed in both cases. In this context, this thesis aimed to (a) determine the in vitro susceptibility of C. lamprauges against different antimicrobial drugs, as well as identify possible synergistic associations; (b) the use of standardized disk diffusion technique with minocycline as a screening method for the presumptive identification of P. insidiosum; (c) quantify, extract and evaluate the immunomodulatory potential of β-glucans from P. insidiosum in vitro in cell cultures in vitro and in mice; (d) develop an experimental pythiosis model in mice and evaluate the immune response to infection. As results we achieved: i) assessing the in vitro susceptibility of C. lamprauges isolated from sheep infections, there is reduced susceptibility to most antimicrobial drugs tested, with terbinafine the drug with improved activity (MIC <0.06- 0.5 μg/mL). The highest rates of synergism were observed with the combination of sulfamethoxazole and trimethoprim (100%) and between the terbinafine with azole antifungal drugs (71%); ii) the standardization of the use of disk diffusion technique with minocycline disks as a screening method for the presumptive identification of P. insidiosum was effective because there was no mycelial growth of P. insidiosum around the minocycline disk during the seven days of incubation, thus differentiating it from C. lamprauges and other true fungi; iii) β-glucan content from P. insidiosum enzymatically assessed was 23.09 ± 3.71% of total glucan, divided into α-glucans (4.10 ± 0.83%) and β-glucans (18.99 ± 3.59); iv) β-glucan extract from P. insidiosum yielded an extract containing 82% of β-glucans and 18% of residual amino acids and peptides, and the structural analysis revealed that it was a (1,3)(1,6)-β-glucan; This (1,3)(1,6)-β-glucan demonstrates a potential to stimulate the immune system in vitro, as observed by the increase in equine, human and mouse lymphocyte proliferation and ability to induce Th17 type response when administered to mice; vi) the use of BALB/c mice immunosuppressed with cyclophosphamide and hydrocortisone association was shown to be an effective experimental model for the study of pythiosis, with 60% of mortality; vii) The cytokine production observed during the development of the experimental pythiosis in mice was characterized by an expression of IL6, IL-10 and TNF-α, indicating an inflammatory response and possible suppression of the host immune response as responsible for the infection property.